Vitality as a measure of animal welfare during purse seine pumping related crowding of Atlantic mackerel (Scomber scrombrus) - Neil Anders; Sigurd Hannaas; Jostein Saltskår; Erik Schuster; Maria Tenningen; Bjørn Totland; Aud Vold; Jan Tore Øvredal; Mike Breen (Scientific Reports, 2022)
Abstract The impacts of wild capture fishing on animal welfare are poorly understood. During purse seine fishing for Atlantic mackerel (Scomber scrombrus), catches are crowded to high densities to facilitate pumping onboard. This study aimed to monitor fish welfare during crowding events in the Norwegian purse seine fishery, and to identify relevant drivers. We first correlated a suite of neuro-endocrine, physiological and physical stress responses (integrated into a single measure of welfare using multivariate analysis) to the behavioural vitality of individual mackerel in controlled crowding trials in aquaculture cages. Vitality was found to be a useful measure of welfare. We then assessed individual fish vitality onboard a commercial purse seiner. Catch welfare, measured using vitality, was observed to be negatively impacted during pumping related crowding. Larger catches and longer crowding exposure times resulted in greater negative impacts. Vitality was not significantly impacted by crowding density or dissolved oxygen concentrations inside the net, although methodological limitations limited accurate measurement of these parameters. Blood lactate levels correlated negatively with vitality, suggesting that high-intensity anaerobic locomotory activity was associated with the reduction in welfare. Based on these findings, catch welfare could be improved by targeting smaller schools to minimise crowding exposure times.